Demonstrasi Tentang Stimulasi Tumbuh Kembang Motorik Kasar Pada Anak Usia 4 - 5 Tahun - Fany Anitarini; Anita Dwi Ariyani (WASATHON Jurnal Pengabdian Masyarakat, 2023)
Nursing as part of health services plays an important role in efforts to improve child development according to developmental tasks. Various health services can be provided by nurses, both general and specialist services provided by pediatric nurse specialists, to help improve child development. In a community setting, nurses provide services not only at the Puskesmas but also at institutions such as early childhood services, such as the Dharma Wanita 3 jajag Kindergarten. The method used in this activity is the delivery of material by showing material power points, discussions and feedback from the guardians of students to apply stimulation of gross motor development. This demonstration is very important given to Dharma Wanita 3 Jajag Kindergarten and parents and toddlers really need developmental stimulation to achieve optimal growth and development, considering that this place has never received counseling and training on stimulating the development of children aged 4-5 years. This falling stimulus program is very effective for improving gross motor skills in children aged 4-5 years. This program was held in collaboration with Dharma Wanita 3 Jajag Kindergarten, Gambiran District, Banyuwangi Regency